Beckman Facilities, Mountainside, New Jersey - Interstate Photographers
The exterior views (2012-002_1155 and 2012-002_1156) are the work of Interstate Photographers; the others are unattributed.
Keywords: Buildings; Employees; Offices; Beckman Instruments, Inc.